Leadership Development Programs: Evaluating their Efficacy in Succession Planning - Tabara, Reijeng (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The effectiveness of Leadership Development Programs (LDP) in a variety of organizational contexts, including industry, organizational size, and organizational culture, has been the focus of significant research. This research aims to explore variations in the effectiveness of LDP in these various contexts. Findings indicate that LDP effectiveness varies significantly between industries, depending on the unique leadership needs in each sector. Additionally, organizational size also influences the effectiveness of LDP, with small organizations tending to benefit from a more direct and responsive LDP process, while large organizations require a more structured program to address the complexity of their structure. Organizational culture is also an important factor influencing LDP effectiveness, with underlying values, norms, and assumptions influencing the design and implementation of the program. The implication of these findings is the importance of a flexible and tailored approach to different organizational contexts in designing and implementing LDPs. However, this study has certain limitations, such as limited data and focus on a specific context, that need to be taken into account in the interpretation of the findings. Future studies are recommended to further explore the influence of different leadership needs across industries, sizes, and organizational cultures on LDP effectiveness, as well as explore more innovative and inclusive leadership development strategies to meet the demands of increasingly complex and diverse work environments.